Presidential Decree-Law No. 203/2014 Regarding the Stimulation of Producing Electricity from Renewable Energy sources = قرار رئيس جمهورية مصر العربية بالقانون رقم 203 لسنة 2014 بشأن تحفيز إنتاج الكهرباء من مصادر الطاقة المتجددة / Presidency. - Egypt. Presidency. (2025)
Decree law of the president of the Arab Republic of Egypt No. 203 of the year 2014 Regarding the stimulation of producing electricity from renewable energy sources قرار رئيس جمهورية مصر العربية بالقاون رقم 203 لسنة 2014 بشان تحفيز إنتاج الكهرباء من مصادر الطاقة المتجددة